2018
DOI: 10.1155/2018/5767360
|View full text |Cite
|
Sign up to set email alerts
|

eSkin: Study on the Smartphone Application for Early Detection of Malignant Melanoma

Abstract: Background. Malignant melanoma is among the fastest increasing malignancies in many countries. With the help of new tools, such as teledermoscopy referrals between primary healthcare and dermatology clinics, the diagnosis of these patients could be made more efficient. The introduction of a high-quality smartphone with a built-in digital camera may make the early detection more convenient. This study presents novel directions for early detection of malignant melanoma based on a smartphone application. Objectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In Saudi Arabia and Philippine, there is an extremely small percentage of health workers using mHealth applications and a low level of awareness of such technologies. Again, the review illustrates that mHealth devices provide accurate diagnostic procedures for a few disease conditions across LMICs to promote quality healthcare services [ 133 , 136 ]. The review further illustrates some risks associated with the use of mHealth such as non-adherence to antiretroviral treatment, the wrong amount of medications, inaccurate data interpretation, wrong insertion of data by patients, and others across many LMICs [ 106 , 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Saudi Arabia and Philippine, there is an extremely small percentage of health workers using mHealth applications and a low level of awareness of such technologies. Again, the review illustrates that mHealth devices provide accurate diagnostic procedures for a few disease conditions across LMICs to promote quality healthcare services [ 133 , 136 ]. The review further illustrates some risks associated with the use of mHealth such as non-adherence to antiretroviral treatment, the wrong amount of medications, inaccurate data interpretation, wrong insertion of data by patients, and others across many LMICs [ 106 , 107 , 108 ].…”
Section: Discussionmentioning
confidence: 99%
“…Jaworek-Korjakowska et al. reported that mHealth applications were also utilized to accurately diagnose or detect Malignant Melanoma cases among individuals in Poland [ 136 ]. A study in Madagascar has shown that mHealth devices were deployed to accurately diagnose soil-transmitted helminth infections to promote healthcare delivery [ 137 ].…”
Section: Overviewmentioning
confidence: 99%
“…The human skin is the largest body organ and can be agonised from different factors like sun (Ultraviolet) radiations, tanning, lifestyle, smoking, alcohol usage, physical activities, viruses and working environment (Jaworek-Korjakowska & Kleczek, 2018;Salem, Azar, & Tokajian, 2018). These factors compromise its integrity and have a profound, devastating impact on its well-being.…”
Section: Introductionmentioning
confidence: 99%
“…In general, the skin tumors are classified into malignant melanomas and non-melanoma, and they rank according to the cell in which they originated [2]. The most common…”
Section: Introductionmentioning
confidence: 99%
“…non-melanomas are basal cell carcinoma and squamous cell carcinoma. Regarding the malignant skin diseases, Melanoma is the most dangerous skin cancer but less frequently; if it is detected early, it can be curable, having a death rate of 85% of all fatal skin cancer cases [2], [3]. In particular, the main features of the skin lesions for Melanoma are asymmetrical shape, irregular edges, various shades of pigmentation, and its diameter can be greater than 6 mm.…”
Section: Introductionmentioning
confidence: 99%